2009
DOI: 10.11646/zootaxa.2314.1.2
|View full text |Cite
|
Sign up to set email alerts
|

New geographic and host records for scelionid wasps (Hymenoptera: Scelionidae) parasitoids of insect pests in South America

Abstract: This contribution provides new parasitoid/host associations for scelionid species distributed in Argentina, Brazil, Colombia and Uruguay, and new geographic records. The parasitoid species examined belong to the genera Gryon Haliday, Phanuropsis Girault, Trissolcus Ashmead, and Telenomus Haliday, and all of them attack insect pests. Three cases of multiple scelionid species emerging from a single egg mass of Pentatomidae are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
1
9
0
2
Order By: Relevance
“…The present paper extends the geographic range of G. vitripenne to Sete Lagoas municipality, Minas Gerais State, Brazil, about 7,600 km SE from Brownsville and Harlingen, Texas, EUA, the types localities (Masner 1983), and about 1,200 km SE from Campo Verde, Mato Grosso State and 1,400 km NE from Porto Alegre, Rio Grande do Sul State, the previously known records in Brazil (Polaszek and Kolberg 2008;Margaría 2008;Margaría et al 2009). Based on the results of this study we have increased the knowledge about the associations and distribution of G. vitripenne, a potential agent of biological control of L. zonatus.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The present paper extends the geographic range of G. vitripenne to Sete Lagoas municipality, Minas Gerais State, Brazil, about 7,600 km SE from Brownsville and Harlingen, Texas, EUA, the types localities (Masner 1983), and about 1,200 km SE from Campo Verde, Mato Grosso State and 1,400 km NE from Porto Alegre, Rio Grande do Sul State, the previously known records in Brazil (Polaszek and Kolberg 2008;Margaría 2008;Margaría et al 2009). Based on the results of this study we have increased the knowledge about the associations and distribution of G. vitripenne, a potential agent of biological control of L. zonatus.…”
Section: Resultssupporting
confidence: 69%
“…Almost nothing is known about the biology and habits of G. vitripenne: when Masner (1983) described the species he stated that part of the type series was obtained from eggs of an unidentified coreid. Polaszek and Kolberg (2008) reported the primary parasitism of G. vitripenne in Holhymenia rubiginosa Breddin, 1904 and Anisoscelis foliaceus (Fabricius, 1803) (Heteroptera: Coreidae) eggs, Margaría (2008) and Margaría et al (2009) reported that exemplars of G. vitripenne were reared form eggs of unidentified bugs on Oryza sativa (Poaceae).…”
Section: Resultsmentioning
confidence: 99%
“…quadripustulata is listed as a host of Tr. brochymenae (Margaria, Loiacono, & Lanteri, ); and Hymenoptera Online (http://hol.osu.edu) lists Br. quadipustulata and Ba.…”
Section: Discussionmentioning
confidence: 99%
“…brochymenae (Margaria, Loiacono, & Lanteri, 2009) Characterization of the predominant egg parasitoids associated with pentatomids provides valuable information on trophic interactions that are of interest not only in a biological control context, but also from an ecological perspective, particularly following the introduction and spread of invasive species. The infiltration of invasive species into new environments often results in competition with native fauna and can alter the community structure of native species (Caro & Sherman, 2011 (Abram et al, 2014).…”
Section: Species-level Host-parasitoid Associationsmentioning
confidence: 99%
“…Telenomus podisi Ashmead (Hymenoptera: Scelionidae) is an egg parasitoid available for field releases in augmentative biological control that acts as a biocontrol agent of different pentatomid stink bug species. However, the family Pentatomidae includes pests as well as biocontrol agents, such as the predator Podisus nigrispinus (Dallas) (Hemiptera: Pentatomidae), which also is parasitized by T. podisi (Torres et al 1996;Medeiros et al 1997;Pacheco & Corrêa-Ferreira 2000;Koppel et al 2009;Margaría et al 2009).…”
Section: Introductionmentioning
confidence: 99%